Presidential Election and the Battle of Online Media Discourse in Indonesia - Rudianto Rudianto (Budapest International Research and Critics University, 2021)
In every presidential election event, the neutrality of the mass media is always a controversy. This happens in any country, including Indonesia.It is interesting to see how online mass media in Indonesia discourse political events after the 2014 presidential election. With the power of speed in presenting news, online media such as detik.com, kompas.com, vivanews.co.id are competing to present their frames on political events that took place. The focus of this article's study is on online mass media coverage of political events that occurred after the 2014 presidential election. The study was conducted with content analysis of five online media, namely detik.com, kompas.com, okezone.com and republika.co.id. The conclusion obtained is the post-2014 presidential election media discourse, especially after the voting on 9 July 2014, generally revolves around the quick count results of the survey institution's version and the winning claims of each candidate. The mass media, especially detik.com, kompas.com and vivanews.com, compile a discourse with a tendency to take sides with one of the pairs based on the results of the survey institute's quick count.